ANALISIS ISU DAN KEBIJAKAN PEMBANGUNAN BERPERSPEKTIF GENDER KABUPATEN BANJARNEGARA - MARWAH, SOFA (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
Human Development Index (HDI) and Gender Development Index (GDI) of regencies show disparity with the achievements of the national and provincial levels. One of which is the HDI and GDI of Banjarnegara Regency, which is lower than Central Java Province, even the third-lowest among regencies in Central Java. IN addition, the disparity between HDI and GDI shows that the development results have not been accessed by both men and women fairly and equally. The problem of gender development in Banjarnegara Regency is reflected in the low level of participation of school-aged children both male and female, the high rate of maternal mortality, the low absorption of women job seekers in employment, violence against women, the lack of women political representation, and so forth. In connection with these conditions, Banjarnegara regency has spawned the policies of gender responsive local development strategies as a form of commitment and hard work of local governments to resolve the issue of gender in the area. The commitment and efforts of local government deserves appreciation.